GWAS of clinically defined gout and subtypes identifies multiple susceptibility loci that include urate transporter genes. Issue 5 (29th November 2016) - Nakayama, Akiyoshi; Nakaoka, Hirofumi; Yamamoto, Ken; Sakiyama, Masayuki; Shaukat, Amara; Toyoda, Yu; Okada, Yukinori; Kamatani, Yoichiro; Nakamura, Takahiro; Takada, Tappei; Inoue, Katsuhisa; Yasujima, Tomoya; et al.
Abstract : Objective: A genome-wide association study (GWAS) of gout and its subtypes was performed to identify novel gout loci, including those that are subtype-specific. Methods: Putative causal association signals from a GWAS of 945 clinically defined gout cases and 1213 controls from Japanese males were replicated with 1396 cases and 1268 controls using a custom chip of 1961 single nucleotide polymorphisms (SNPs). We also first conducted GWASs of gout subtypes. Replication with Caucasian and New Zealand Polynesian samples was done to further validate the loci identified in this study. Results: In addition to the five loci we reported previously, further susceptibility loci were identified at a genome-wide significance level (p<5.0×10 −8 ): urate transporter genes ( SLC22A12 and SLC17A1 ) and HIST1H2BF-HIST1H4E for all gout cases, and NIPAL1 and FAM35A for the renal underexcretion gout subtype. While NIPAL1 encodes a magnesium transporter, functional analysis did not detect urate transport via NIPAL1, suggesting an indirect association with urate handling. Localisation analysis in the human kidney revealed expression of NIPAL1 and FAM35A mainly in the distal tubules, which suggests the involvement of the distal nephron in urate handling in humans. Clinically ascertained male patients with gout and controls of Caucasian and Polynesian ancestries were also genotyped, and FAM35A was associated with gout in all cases. A meta-analysis of the three populations revealed FAM35A to be associated with gout at a genome-wide level of significance (p meta =3.58×10 −8 ). Conclusions: Our findings including novel gout risk loci provide further understanding of the molecular pathogenesis of gout and lead to a novel concept for the therapeutic target of gout/hyperuricaemia.